Comparison of two different catalyst preparation methods for graphene nanoplatelets supported platinum catalysts. (22nd June 2016) - Daş, Elif; Alkan Gürsel, Selmiye; Işikel Şanli, Lale; Bayrakçeken Yurtcan, Ayşe
Abstract: In this study, we compared two facile and effective approaches which are supercritical carbon dioxide (scCO2 ) deposition and microwave irradiation methods to synthesize Pt nanoparticles uniformly dispersed on graphene nanoplatelets (G) having 750 m 2 /g surface area as the support material. The prepared catalysts were characterized by using XRD, TGA, TEM, CV and PEM fuel cell performance tests. Microwave irradiation (Pt/G1) and scCO2 deposition (Pt/G2) methods resulted in the particle sizes of 3.1–3.4 nm and 1.5–1.6 nm, respectively. Higher electrochemically active surface area and PEM fuel cell performance were obtained for the Pt/G2 catalyst. An accelerated aging test, carbon corrosion, is also applied to the catalysts and Tafel slope losses were determined. Pt/G1 catalyst resulted in 50 mV Tafel slope loss whereas no significant loss was observed for Pt/G2 catalyst after carbon corrosion test. Highlights: Graphene nanoplatelet supported Pt nanoparticles synthesized via two methods. Microwave irradiation method is used. Supercritical carbon dioxide deposition (scCO2 ) method is used. ScCO2 method gave better structured catalysts with high PEMFC performance.